Efek Diuretik Nigella sativa sebagai Terapi Hipertensi - Fadila Rahayu (CV. Jasa Sukses Abadi, 2020)
Hypertension is a condition of increased blood pressure that can cause damage to organs such as heart, blood vessels, kidneys and the central nervous system. Prevention and treatment of hypertension requires something with minimal side effects. Nowadays, herbal medicine are so popular because its contain antioxidant and etc that can be another choice to treat the disease. One of them is Nigella sativa. The main contents are thymoquinone and polyphenols. N. sativa seeds contain protein (26.7%), fat (28.5%), carbohydrates (24.9%), crude fiber (8.4%) and total ash (4.8%). The seeds also contain many vitamins and minerals such as Cu, P, Zn and Fe etc. The seeds contain carotene which the liver converts into vitamin A. The roots and shoots are reported to contain vanillic acid. The seeds are reported to contain fatty oils rich in unsaturated fatty acids, especially linoleic acid (50-60%), oleic acid (20%), eicodadienoic acid (3%) and dihomolinoleic acid (10%). Nigella sativa has a diuretic effect to make diuresis so this can make lower blood pressure in hypertensive condition. Moreover, Nigella sativa has another mechanism to make blood pressure lower in hypertensive condition.